Prevalence of reproductive health issues and knowledge, attitude, and practice of personal protective equipment use among women working in the fireworks industry: A cross-sectional study - Sowmiya Kothandaraman; Alex Joseph; Dhasarathi Kumar; Saravanan Chinnaiyan (Journal of Family Medicine and Primary Care)
Background: Exposure to chemicals among women working in the fireworks industry can lead to the risk of birth defects. In India, the congenital birth defects prevalence is 25 per 1000 live births. Objectives: To address the risk of birth defects, stillbirth, and miscarriage due to chemical exposure and assess the knowledge, attitude, and practice of using personal protective equipment (PPE) among women, working in the fireworks industry. Methods: The cross-sectional study was conducted on married women working in the fireworks industry to study the prevalence of birth defects, stillbirth, and miscarriage. Data were collected using a semistructured questionnaire. Data analysis involves descriptive statistics. Results: Out of 300 workers, the prevalence of miscarriage is 22%, that of stillbirth is 8.3%, and that of birth defect is 2%. Only 20.7% of people know the use of PPE except for wearing cotton clothes, where the knowledge is 99%. The major source of knowledge about PPE is through general external officer meetings (69.4%), and the major source of knowledge about wearing only cotton clothes is through office management (68.7%). Among the knowledgeable people, only 4.8% use PPE while working. Education and experience increase the knowledge about the use of PPE. Conclusion: Continuous exposure to chemicals in the fireworks industry can increase the chance of miscarriage, stillbirth, and birth defects. Effective health education initiatives and ongoing counseling can help people develop positive outcomes.